Cure behaviors and mechanical properties of carbon fiber-reinforced nylon6/epoxy blended matrix composites. (1st March 2017) - Kim, Kwan-Woo; Kim, Dong-Kyu; Kim, Byoung-Suhk; An, Kay-Hyeok; Park, Soo-Jin; Rhee, Kyong Yop; Kim, Byung-Joo
Abstract: In this work, the composition effects of a nylon6 and epoxy blend system on the cure behaviors and mechanical properties of carbon fiber-reinforced nylon6/epoxy composites were investigated. Ethanol was used as a melting agent for nylon6 (alcohol-soluble nylon), and the content of nylon6 in the mixture was 0–50 wt%. The curing properties of the blend system were investigated by differential scanning calorimeter (DSC), thermogravimetric analysis (TGA), and fourier transform infrared spectroscopy (FT-IR). The surface morphologies of the fractured surfaces were observed by scanning electron microscopy (SEM). The mechanical properties of the composites were measured with the Charpy pendulum impact test to observe the cumulative energy absorption until final destruction of the composites. The Charpy energy of the N4:E6 sample was enhanced by 52% compared to that of the pure epoxy. This resulted from the curing relation between the composition of nylon6 and epoxy.